Direct Imaging of Inhomogeneous Obstacles in a Three-Layered Ocean Waveguide (Communications in Computational Physics, 2019)
In this work, we have proven the inhomogeneous obstacle can be uniquelydetermined by the measured acoustic pressure data and have proposed an extendedmultilevel sampling method. The extended recovery approach only applies the matrix-vector operations to estimate the inhomogeneous media from the received partial data.In practice, the method is capable of reconstructing the objects of different shapes andlocations, robust against noise, computationally fairly cheap and easy to carry out. Wecan consider it as a simple and direct algorithm to supply satisfactory initial locationsfor the application of any existing more refined and precise but computationally moredemanding techniques to achieve accurate reconstructions of physical features of scatterers.